PERILAKU HIDUP BESIH DAN SEHAT DALAM RUMAH TANGGA (PHBS) PADA MASYARAKAT DESA GUNUNG KESIANGAN, KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Fitriani Gustia Ningsih; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Clean and healthy behavior is an attempt to provide a learning experience or creating a condition for individuals , families , groups and communities , with open lines of communication , provide information and to educate , to improve knowledge , attitudes and behavior , through leadership approaches (advocacy) , bina atmosphere (social support) and empowerment (empowerman) as an attempt to help people identify and resolve their own problems , in respective order , in order to implement ways of healthy living , in order to maintain , and improve health memilihara . The problem addressed in this paper is to describe the implementation of a clean and healthy living behaviors and the factors that influence the behavior of living clean and healthy . The goal is to determine the implementation of clean and healthy behavior and to determine the factors that influence behavior - fator clean and healthy living . The population is families with children under five in rural mountain communities oversleep totaling 47 families (head of household) , using census data capture techniques . The method used is descriptive quantitative methods with quantitative data analysis . The research instrument used was a questionnaire , interview and documentation . The theory used for this problem is the theory of Max Weber's theory is a theory of social action . The results of the study in general , the writer can say that the implementation of clean and healthy behavior in the community has not been done oversleep mountain village where the birth of respondents were in favor by health workers only 20 % , which is 22.85 % Exclusive breastfeeding , toddler weighed every month 40 % , which uses 42.85 % water sources , washing hands with soap and clean water 12.86 % , 38.58 % healthy latrines , mosquito larvae eradication 18.58 % , mengomsumsi fruit and vegetables every day 11.43 % , and do not smoke in the room 20 % . Factors that influence the behavior of living clean and healthy are income, education, and health centers distance.